A retrospective, real‐world experience of perampanel monotherapy in patient with first new onset focal seizure: A Thailand experience. Issue 1 (10th November 2021) - Chinvarun, Yotin
Abstract: Objective: Real‐world data on efficacy and tolerability of perampanel (PER) monotherapy in treatment‐naïve patients with focal onset seizures (FOS) and/or focal‐to‐bilateral tonic‐clonic seizures (FBTCS) to assess efficacy effectiveness and tolerability. Methods: This is a retrospective review of study patients with new FOS with or without FBTCS, aged ≥15 years, who had been prescribed PER as monotherapy. Treatment outcome included retention rate, responder, and seizure‐free rate at observational point 3, 6, and 12 months (OP3, OP6, and OP12). Treatment‐emergent adverse events (TEAEs) and adverse drug reactions were recorded. Results: A total of 41 patients enrolled in the study (male:female; 17:22, mean age =46.1 ± 21.8 years), with new FOS and/or FBTCS. The proportions of individuals remaining on PER monotherapy at 3, 6, and 12 months were evaluated. The median PER dosage was 4 mg (range 2‐8 mg). The retention rates at OP3, OP6, and OP12 were 88%, 73%, and 61%, respectively. The seizure freedom rates at OP3, OP6, and OP12 were 78%, 80%, and 76%, respectively. About 14% had discontinued the PER monotherapy because of lack of efficacy. Sixteen individuals (41%) had TEAEs; common AEs were dizziness, somnolence, and ataxia; and only one case had depression. The AEs with somnolence and ataxia were found higher in elderly (15% and 30%) than adult patients (7% and 3%), respectively. Only 14% had intolerant adverse events, and it was found higher in elderly (23%). Significance: Real‐world data of PER monotherapy in treatment‐naïve patients with focal onset seizures demonstrated good effectiveness and a good safety profile at relatively low doses. By starting with low dosage and slow titration of PER help to minimize the impact of adverse effects, maximize adherence, and increase patient retention. PER has a once‐daily dosing schedule that supports patient adherence contributes to achieving seizure freedom.